Comparing the Effectiveness of Multitask Role-play and Traditional Technique in Teaching Speaking to Students with Different Self-Confident Levels - Siti Nurhayati; Rudi Hartono; Rahayu Puji H (English Education Journal, 2023)
In English education, speaking skills are very crucial developed, because it plays essential roles in communication. Based on the research at SMP Al Falah, multiple problems might have taken place concerning the teaching and learning of speaking skills. One was the traditional technique that made the learning process run monotonously and boring. Besides that, many students still needed help, such as they answered with many lexico-grammatical mistakes and ideas required to speak up. They also needed to be more confident. Therefore, this research applied to multitask role play, it is the role-play technique combined with activities or tasks which allow the students to get exposed to authentic models from youtube, communicate with each other, and solve a problem or complete a task. In this case, the writers figured out that this role play used authentic materials as models that can be taken from the internet, such as the videos from "you tube' and information gap activities as further skills practice. This research aims to explain how significant the students' achievement is taught by using multitask role play and traditional techniques with different self-confidence levels in teaching speaking skills. This research design was a quasi-experimental design with a 2x2 factorial design involving the eighth-grade students SMP Al Falah, Cirebon. In collecting the data, the writers used a speaking test to get students' scores and questionnaires. The data was analyzed using ANOVA to answer the main hypotheses. The results show that implementing Multitask Role play is more effective than Traditional technique with scores of 0.000 for MTRP and 0.073 for TT. It was because of the multitask role play focused on students-center, used accurate models from youtube, PPT to explain the materials, and let students create the dialog using their own words by making the information gap. It is inversely proportional to the Traditional technique which is still teacher-center, explained the materials monotonously with textbook, and only asked students to memorize the delivered dialog. Based on the findings, the writers believe that this study can be a reference for the study of English education and language education development in teaching speaking skills. One of them is how to apply role play technique combined with another activity.